Indigenous perspectives on education for well-being in Canada - Falkenberg, Thomas; Deer, Frank (Education for Sustainable Well-Being Press (ESWB Press), 2023)
In this edited book, scholars and researchers provide and engage with Indigenous perspectives on the possibilities of education to foster well-being among Indigenous people(s). Chapters address issues of understanding Indigenous perspective on “the good life;” on holistic lifelong learning; on Bannock; on healthy bodies; on the spiritual relationship with Mother Earth; on the preservation of Indigenous cultural heritage. Other chapters engage with Urban Indigenous food sovereignty; with Anishinaabe perspectives on the cultural dimensions of well-being in schools; with integrating Indigenous cultural education in a youth treatment program; with the integration of Indigenous perspectives in teacher education programs; with building healthy learning communities for Indigenous university students; and with what non-Indigenous Canadians can learn from these Indigenous perspectives.